Sequência Expandida em Leitura Literária na construção das cidades de Porto Alegre e Cascavel Da ficção à realidade - Souza, Vanusa de (2016)
This dissertation presents a Pedagogical Intervention Project, implemented in the 9th grade of elementary school , a public school in Cascavel City, Paraná. It was used the theoretical assumptions of Rildo Cosson were used on the Expanded Sequence, in which we reflect on the spatial configuration in the book "Mistérios de Porto Alegre" by Moacyr Scliar (2004) and contributed to the perception of the building symbolic place where students / readers live. Regarding to the methodology were outlined the proposals by Michel Thiollent in Action Research, applied to Literary Reading practices in school settings. This study considers the city and its spatial configuration and to analyze them, elaborations by Michel de Certeau, Sandra Jatahy Pesavento, Néstor García Canclini, and others are mentioned because they are considered as the materialization of speech, which is why, under this perspective, it cannot be seen as a reality in itself, but as a process of social production. The power relationships established in this movement of organization, planning and performance in urban space, aimed at construction and reconstruction of places. This dynamic, which moves the interactions to which students are immersed, could be studied through the intervention made between the teacher / researcher, teachers / staff, teaching staff, the librarian, the family and the local community with favorable finding, which confirmed the significance of the research